2022
DOI: 10.1097/md.0000000000029305
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of life determinants in hemodialysis patients of a developing country: A cross-sectional study during ongoing COVID-19 pandemic

Abstract: Background and Objectives: Patients of end-stage renal disease are prone to have a very low quality of life (QoL). Variety of factors influence the QoL among sufferers of chronic kidney disease comprising of type of dialysis, sufficiency/adequacy of dialysis, and associated burden of disease. We conducted this study amidst the pandemic to determine the associated factors for poor QoL in hemodialysis patients during the ongoing pandemic.Patients and Methods: This cross-sectional study was conducted in a hemodia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…A search of the literature for corresponding studies during this time period found similar results to those of the present study. Ashgar et al (2022) observed low QoL ( p > 0.001) in all subscales ( p = 0.003) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A search of the literature for corresponding studies during this time period found similar results to those of the present study. Ashgar et al (2022) observed low QoL ( p > 0.001) in all subscales ( p = 0.003) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hasil penelitian ini berbeda dengan penelitian-penelitian sebelumnya. Penelitian yang dilakukan oleh Asghar et al 22 pada tahun 2021, yang menilai asosiasi antara IMT dengan kualitas hidup pasien hemodialisis dengan menggunakan Quality of Life Index-dialysis version-III (QLI), menunjukkan terdapat asosiasi bermakna antara IMT dengan kualitas hidup pasien PGK yang melakukan terapi dialisis dua kali per minggu (p<0,001). Penelitian oleh Günalay et al 23 di İzmir Tepecik Training and Research Hospital pada tahun 2016, yang menilai hubungan antara malnutrisi dan kualitas hidup pasien hemodialisis menggunakan EQ-5D, menunjukkan bahwa skor kualitas hidup lebih rendah ditemukan pada pasien dengan malnutrisi dibandingkan dengan yang tidak malnutrisi (p=0,001).…”
Section: Bahasanunclassified